Effect of Nanolubricant on Evaporator and Condenser Pressure of Automotive Air Conditioning System - M. Z., Sharif; Azmi, W. H.; Mohamad Redhwan, Abd. Aziz (Universiti Malaysia Pahang, 2016)
Automotive Air Conditioning system efficiency can be improved by dispersing nanolubricant in the refrigeration system. The condenser and evaporator pressure was closely related to the performance of the system. In this paper, the nanolubricant and conventional lubricant performance in the AAC system was compared. The condenser and evaporator pressure was reduced by an average of 8.47 % and 3.84 % respectively when being replaced with nanolubricant compared to conventional lubricant. The nanolubricant also improve the compressor work reduction up to 17.1 %. As conclusion, it is recommended to use the nanolubricant as replacement to improve the energy efficiencies in AAC system.